Decolonizing foreign language education the misteaching of English and other colonial languages - Macedo, Donaldo P. (Donaldo Pereira) 1950- (Routledge, 2019)
"Decolonizing Foreign Language Education interrogates current foreign language and second language education techniques that prioritize white, western thought. Edited by acclaimed critical theorist and linguist Donaldo Macedo, this volume includes cutting-edge work by a select group of scholars working to rigorously challenge the marginalization of foreign language education and the displacement of indigenous languages through the teaching of colonial languages. Each chapter confronts the hold of colonialism and imperialism that inform and shape the relationship between foreign language education and literary studies by asserting that applied linguistics is just as important a tool for ESL/EFL teachers as literature or linguistic theory"--Provided by publisher.